Ethanol combined with heparin as a locking solution for the prevention of catheter related blood stream infections in hemodialysis patients: A prospective randomized study. Issue 4 (11th January 2017) - Sofroniadou, Sofia; Revela, Ioanna; Kouloubinis, Alexandros; Makriniotou, Ioanna; Zerbala, Sinodi; Smirloglou, Despina; Kalocheretis, Petros; Drouzas, Apostolos; Samonis, George; Iatrou, Christos
Abstract: Introduction: Ethanol lock solution has been mainly administered in paediatric and home parenteral nutrition patients in order to prevent catheter related blood stream infections (CRBSI). Its utility in hemodialysis (HD) patients with non‐tunneled‐uncuffed catheter (NTC) has been poorly explored. Methods: We conducted a prospective randomized study in chronic HD patients requiring a newly inserted NTC‐while awaiting for the maturation of an already established arteriovenous fistula (AVF) or arteriovenous graft (AVG) or tunneled‐cuffed catheter insertion. Patients were randomized in two groups: Group A, where the lock solution was ethanol 70% + unfractionated heparin 2000 U/mL and group B, that received only unfractionated heparin 2000 U/mL. Primary end point was CRBSIs whereas exit site infections, thrombotic and bleeding episodes were the secondary end points. Findings: One hundred three HD patients were enrolled in the study (group A, n = 52; group B, n = 51). The median number of catheter days was 32 for group A (range: 23–39) and 34 (range: 27–40) for group B with no statistically significant difference between the two groups. Group A (ethanol + heparin) demonstrated 4/52 episodes (7.69%) of CRBSI whereas Group B (heparin) 11/51 episodes (21.57%) (P = 0.04). CRBSI rates per 1000 catheter days were 2.53/1000 catheter days for group A and 6.7/1000 catheter days for group B (P = 0.04). Mean cumulative infection‐free catheter survival in the ethanol group did not differ significantly compared to the heparin group (log‐rank test = 2.99, P = 0.08). Thrombotic episodes did not differ between the two groups. Discussion: Locking of NTCs in HD patients with ethanol 70% + unfractionated heparin reduces CRBSI rates without increasing the thrombotic episodes.